Atividade antifúngica e toxicidade dos monoterpenos citral e carvacrol - Lima, Igara Oliveira (2011)
Candidiasis has been important fungal infection related in hospital environment, and the main specie involved is Candida albicans. This fact has encouraged researchers alternatives in the treatment of candidiasis. The terpenes are strong candidates like antifungal agents, however it is necessary to study the toxicity of this molecules. The aim of this study was to investigate the antifungal activity, the mode of action of citral and carvacrol, the time-kill and synergism of carvacrol, besides toxicological studies. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of citral was 512 μg/mL e 1024 μg/mL, respectively. The MIC and MFC of carvacrol was 256 μg/mL e 512 μg/mL, respectively. These phytoconstituints did not act sorbitol view. Carvacrol interacts with ergosterol. However, the phytoconstituints citral and carvacrol are able interacting with cholesterol. The monoterpenes did not showed synergism neither antagonism with amphotericine B. They inhibited the psedo-hife formation in C. albicans. Citral and carvacrol altered some biochemical paramenters, water and food consumption in mice. They showed citotoxicity action in MDCKs cells and they did not have oxidative and antioxidant effect.